2018
DOI: 10.1016/j.apcata.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of iron-based metal-organic framework MIL-53 as an efficient catalyst to activate persulfate for the degradation of Orange G in aqueous solution

Abstract: A series of MIL-53(Fe) materials were synthesized using a solvothermal method under different temperature and time conditions and were used as catalysts to activate persulfate and degrade Orange G (OG). Influences of the above conditions on the crystal structure and catalytic behavior were investigated. Degradation of OG under different conditions was evaluated, and the possible activation mechanism was speculated. The results indicate that high synthesis temperature (larger than 170 °C) leads to poor crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(54 citation statements)
references
References 62 publications
9
45
0
Order By: Relevance
“…They can be explained by the effect of the synthesis temperature on the structure formation of MIL-53(Fe). Pu et al demonstrated that iron ion and H 2 BDC could not coordinate successfully under a low temperature (100 • C), and therefore the MIL-53(Fe) crystal structure could not fully develop [40]. However, the Ni/Fe-MOF samples still show a high crystalline phase under low synthesis temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be explained by the effect of the synthesis temperature on the structure formation of MIL-53(Fe). Pu et al demonstrated that iron ion and H 2 BDC could not coordinate successfully under a low temperature (100 • C), and therefore the MIL-53(Fe) crystal structure could not fully develop [40]. However, the Ni/Fe-MOF samples still show a high crystalline phase under low synthesis temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The O 1s XPS spectra ( Figure 5C) could also be fitted into three peaks, which are (i) the peak at 533.8 eV corresponding to the O components on C=O/H2O, (ii) the peak at 532.3 eV attributed to the O components on the BDC linkers, and (iii) the peak at 530. 5 eV was assigned to the Both spectra were fitted into three peaks at a binding energy (BE) of 285.01, 288.9, and 291.7 eV, which could be assigned to the carbon components on the phenyl and the carboxylate groups of the BDC linkers [30,40,[44][45][46]. The O 1s XPS spectra ( Figure 5C) could also be fitted into three peaks, which are (i) the peak at 533.8 eV corresponding to the O components on C=O/H 2 O, (ii) the peak at 532.3 eV attributed to the O components on the BDC linkers, and (iii) the peak at 530.…”
Section: Xps Spectramentioning
confidence: 99%
“…In addition, many organic dyes contain chemicals that are toxic or carcinogenic to mammals and other living organisms [6,7]. An important problem is also the non-biodegradable nature of some dyes and their resistance to light 2 of 22 and oxidizing agents [8,9]. Methylene blue (MV), Congo red (CR) and methyl violet (MV) are some of the most common organic dyes present in wastewater and industrial effluents.…”
Section: Introductionmentioning
confidence: 99%
“…Among these AOPs are, photocatalysis, electrocatalysis, photo‐electrocatalysis, electro‐Fenton, Fenton, peroxicoagulation, photo‐Fenton, sono‐Fenton, sonochemical methods, hydrodynamic cavitation, zero valent metals based AOPs, and oxidation processes based on the use of radicals (SO 4 −• , OH • ) . However, the oxidation by the radicals of sulfate SO 4 −• attracted a lot of attention because of the high oxidation potential that is expected at 2.01 V compared to others radicals . In addition, the high stability and the low cost of these radicals make this process interesting from an environmental and economical point of view .…”
Section: Introductionmentioning
confidence: 99%